Synthesis and structural, optical, photocatalytic, and electrochemical properties of undoped and yttrium-doped tetragonal ZrO2 nanoparticles. Issue 11 (1st August 2018) - Reddy, Chandragiri Venkata; Reddy, I. Neelakanta; Shim, Jaesool; Kim, Dongseob; Yoo, Kisoo
Abstract: Template-free undoped and yttrium-doped tetragonal ZrO2 nanoparticles were successfully synthesized using a hydrothermal technique, and their structural, morphological, optical, and electrochemical properties were characterized. The photocatalytic activity for the dye degradation of the Rhodamine B (RhB) was also studied under UV light irradiation. The tetragonal crystal phase of the nanoparticles was confirmed by XRD analysis. The observed peak shift in XRD patterns confirmed the incorporation of dopant into host lattice. The Yttrium-doped ZrO2 nanoparticles showed a higher specific surface area and smaller optical band gap (191.5 m 2 /g and 3.66 eV) than the pristine ZrO2 nanoparticles (108.6 m 2 /g and 4.94 eV). The yttrium-doped ZrO2 nanoparticles exhibited greater photocatalytic activity ( 98%) than the pure ZrO2 nanoparticles within 40 min, due to their high specific surface area and reduced photogenerated charge carrier recombination rate. The Nyquist plot of yttrium-doped sample exhibited lower charge transfer resistance than that of the undoped sample. The photocurrent of the doped sample (28.6 mA/cm 2 ) was 9 times higher than that of pristine ZrO2 sample (3.2 mA/cm 2 ). The doped sample showed stable and higher photocurrent density up to 520 s under light illumination.